Improving the Results of Learning Basic Motion Dribble Football Through the use of Audiovisuals for Class VIII Learners at SMPN 6 Banjarmasin - Muhammad Habibie; Endang Pratiwi; Oddie Barnanda Rizky (UNIB Press, 2022)
Research is conducted collaboratively between researchers and learners. Researchers act as teachers while the learning process is ongoing. This research is carried out through a class action research design which consists of two cycles. Each success rate cycle is adjusted to the competencies expected to be mastered by learners. The media used in this study is audio-visual media. This research was conducted in the even semester of the 2021/2022 school year, increased learning of football dribbles is in March - July. The subject of this study is a class VIII student of SMPN 6 Banjarmasin consisting of 20 learners. The results of research in the form of Pre Test, Cycle I, and Cycle II in the Divergent-style learning process, it turned out that there has been a significant increase in participants' learning outcomes. This can be seen from the increasing value of the Percentage of Learning Completion as well as the average value of student learning outcomes.The results of the cycle II test turned out that the completion value obtained by participants in class VIII of State Junior High School 6 Banjarmasin had reached 9.55%. The use of audio-visual media can improve the learning outcomes of participants in class VIII SMPN 6 Banjarmasin, especially during the pandemic which limits meetings between teachers and students.